2021
DOI: 10.3390/diagnostics11101877
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Temperature: Characterization in a Large Cohort of Healthy Human Eyes and Correlations to Systemic Cardiovascular Risk Factors

Abstract: Purpose: To characterize ocular surface temperature (OST) in healthy eyes and its association with systemic risk factors of cardiovascular and ischemic heart disease. Methods: This prospective cross-sectional study included consenting subjects who were examined at the Institute for Medical Screening in Sheba Medical Center. A Therm-App™ thermal imaging camera (Opgal LTD, Israel) was used for OST acquisition, and the mean OST of the medial canthal, lateral canthal, and central cornea regions were measured. Room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…To study a possible role of TRPM8 in eye blood flow, we determined eye temperature (Teye) by infrared (IR) thermography in WT and Trpm8 −/− mice exposed to different temperatures. Previous studies have shown that ocular haemodynamics can be estimated indirectly by measuring ocular surface temperature 31,32 . Mice were placed on a steel platform and exposed to a cold ramp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study a possible role of TRPM8 in eye blood flow, we determined eye temperature (Teye) by infrared (IR) thermography in WT and Trpm8 −/− mice exposed to different temperatures. Previous studies have shown that ocular haemodynamics can be estimated indirectly by measuring ocular surface temperature 31,32 . Mice were placed on a steel platform and exposed to a cold ramp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that ocular haemodynamics can be estimated indirectly by measuring ocular surface temperature. 31,32 Mice were placed on a steel platform and exposed to a cold ramp. The plate temperature (Tplate) was decreased linearly from 30 to 0°C (1°C/min).…”
Section: Trpm8-positive Fibres Innervate High Blood Flow Ocular Vascu...mentioning
confidence: 99%
“…Statistical significance was set at p < 0.05. Minimum sample size for 80% power and 0.05 alpha, was estimated as 27 eyes/subjects using a single-sided sample size calculator for comparing two paired means [ 27 ] based on an expected mean of the paired differences of 0.5 and expected 1.0 standard deviation of the paired differences based on previous studies [ 14 , 15 , 16 ]. Assuming a 10–15% dropout rate, the total number of participants needed was estimated to be 31 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent large prospective cross-sectional study, Cohen et al, used the Therm-App thermal imaging camera (Opgal Ltd., Karmiel, Israel) to measure OST among individuals undergoing annual general screening tests. In this cohort, they observed a significantly higher OST among persons diagnosed with ischemic heart disease, although no significant association was noted for persons with hypertension, diabetes mellitus or active smoking [ 14 ]. The use of OST as a possible biomarker for retinal disease and glaucoma has also been reported recently [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autism, 2021 [17], Diabetes type II, 2020 [33,34] FLIR Systems, Wilsonsville, OR, USA, ThermoVision A20 160 × 120, 0.12 • C at 30 [45] Ischaemic heart disease, 2021 [54] OptoTherm, Sewickley, PA, USA Thermoscreen 640 × 480, <0.04 • C ±1 • C Fever, 2010 [37], 2011 [38],…”
Section: Thermography Cameras and Technical Properties Imaging Specif...mentioning
confidence: 99%